The pioneer and differentiation factor FOXA2 is a key driver of yolk‐sac tumour formation and a new biomarker for paediatric and adult yolk‐sac tumours. Issue 3 (14th January 2021) - Wruck, Wasco; Bremmer, Felix; Kotthoff, Mara; Fichtner, Alexander; Skowron, Margaretha A.; Schönberger, Stefan; Calaminus, Gabriele; Vokuhl, Christian; Pfister, David; Heidenreich, Axel; Albers, Peter; Adjaye, James; et al.
Abstract: Yolk‐sac tumours (YSTs), a germ cell tumour subtype, occur in newborns and infants as well as in young adults of age 14‐44 years. In clinics, adult patients with YSTs face a poor prognosis, as these tumours are often therapy‐resistant and count for many germ cell tumour related deaths. So far, the molecular and (epi)genetic mechanisms that control development of YST are far from being understood. We deciphered the molecular and (epi)genetic mechanisms regulating YST formation by meta‐analysing high‐throughput data of gene and microRNA expression, DNA methylation and mutational burden. We validated our findings by qRT‐PCR and immunohistochemical analyses of paediatric and adult YSTs. On a molecular level, paediatric and adult YSTs were nearly indistinguishable, but were considerably different from embryonal carcinomas, the stem cell precursor of YSTs. We identified FOXA2 as a putative key driver of YST formation, subsequently inducing AFP, GPC3, APOA1/APOB, ALB and GATA3/4/6 expression. In YSTs, WNT‐, BMP‐ and MAPK signalling‐related genes were up‐regulated, while pluripotency‐ and (primordial) germ cell‐associated genes were down‐regulated. Expression of FOXA2 and related key factors seems to be regulated by DNA methylation, histone methylation / acetylation and microRNAs. Additionally, our results highlight FOXA2 as a promising new biomarker for paediatric and adult YSTs.